The Middle Ages : a graphic guide - Janega, Eleanor (Icon Books, 2021)
"The Middle Ages: A Graphic Guide busts the myth of the 'Dark Ages', shedding light on the period's present-day relevance in a unique illustrated style. This history takes us through the rise and fall of empires, papacies, caliphates and kingdoms; through the violence and death of the Crusades, Viking raids, the Hundred Years War and the Plague; to the curious practices of monks, martyrs and iconoclasts. We'll see how the foundations of the modern West were established, influencing our art, cultures, religious practices and ways of thinking. And we'll explore the lives of those seen as 'Other' - women, Jews, homosexuals, lepers, sex workers and heretics. Join historian Eleanor Janega and illustrator Neil Max Emmanuel on a romp across continents and kingdoms as we discover the Middle Ages to be a time of huge change, inquiry and development - not unlike our own."--